Biosynthesis of Silver Nanoparticles by Marine Actinobacterium Nocardiopsis dassonvillei and Exploring Their Therapeutic Potentials - Khalil, Maha A.; El-Shanshoury, Abd El-Raheem R.; Alghamdi, Maha A.; Alsalmi, Fatin A.; Mohamed, Samia F.; Sun, Jianzhong; Ali, Sameh S. (Frontiers in Microbiology, 2022)
Nanoparticles have recently emerged as a popular research topic. Because of their potential applications in therapeutic applications, biosynthesized silver nanoparticles (Bio-AgNPs) have gained much attention in recent years. Cell-free extracts (CFE) from a marine culture of actinobacteria and silver nitrate were used to reduce Ag+ ions and create Bio-AgNPs. Nocardiopsis dasonvillei KY772427, a new silver-tolerant actinomycete strain, was isolated from marine water and used to synthesize AgNPs. In order to characterize Bio-AgNPs, UV-Vis spectral analysis, Fourier transform infrared (FTIR), transmission electron microscopy (TEM), and dynamic light scattering spectroscopy (DLS) were all utilized. Using UV–Vis spectroscopy, a peak in the surface plasmon resonance (SPR) spectrum at 430 nm revealed the presence of Bio-AgNPs. The TEM revealed spherical AgNPs with a diameter of 29.28 nm. DLS determined that Bio-AgNPs have a diameter of 56.1 nm and a negative surface charge (−1.46 mV). The minimum inhibitory concentration (MIC) of Bio-AgNPs was determined against microbial strains. Using resazurin-based microtiter dilution, the synergistic effect of Bio-AgNPs with antimicrobials was investigated. Pseudomonas aeruginosa had the lowest MIC of Bio-AgNPs (4 μg/ml). Surprisingly, the combination of antimicrobials and Bio-AgNPs had a significant synergistic effect on the tested strains. The insecticidal activity of Bio-AgNPs (200 μg/ml) against Macrosiphum rosae was found to be maximal after 36 h. Additionally, Bio-AgNPs demonstrated significant scavenging activity against 2,2′-diphenyl-1-picrylhydrazyl (DPPH) and hydroxyl (OH–) radicals, with IC50 values of 4.08 and 8.9 g/ml, respectively. In vitro studies using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay revealed a concentration-dependent decrease in cell viability when CaCo2 cells were exposed to Bio-AgNPs. With the decrease in cell viability, lactate dehydrogenase leakage (LDH) increased. The findings of this study open up a new avenue for the use of marine Nocardiopsis dasonvillei to produce Bio-AgNPs, which have significant antimicrobial, antioxidant, insecticidal, and anticancer potential.